Digital versus Analog Procedures for the Prosthetic Restoration of Single Implants: A Randomized Controlled Trial with 1 Year of Follow-Up. (18th July 2018) - Mangano, Francesco; Veronesi, Giovanni
Abstract : Aim . To compare the outcome of digital versus analog procedures for the restoration of single implants. Methods . Over a two-year period (2014-2016), all patients who had been treated in a dental center with a single implant were randomly assigned to receive either a monolithic zirconia crown, fabricated with digital workflow ( test group), or a metal-ceramic crown, fabricated with analog workflow ( control group). All patients were followed for 1 year after the delivery of the final crown. The outcomes were success, complications, peri-implant marginal bone loss (PIMBL), patient satisfaction, and time and cost of the treatment. Results . 50 patients (22 males, 28 females; mean age 52.6±13.4 years) were randomly assigned to one of the groups (25 per group). Both workflows showed high success (92%) and low complication rate (8%). No significant differences were found in the mean PIMBL between test (0.39±0.29mm) and control (0.54±0.32mm) groups. Patients preferred digital impressions. Taking the impression took half the time in the test group (20±5min) than in the contro l (50±7min) group. When calculating active working time, workflow in the test group was more time-efficient than in the control group, for provisional (70±15min versus 340±37min) and final crowns (29±9min versus 260±26min). The digital procedure presented lower costs than the analog (€277.3 versus €392.2). Conclusions . No significant clinical or radiographic differences were found between digital and analog procedures; however, the digital workflow was preferred by patients; it reduced active treatment time and costs. The present study is registered in the ISRCTN (http://www.isrctn.com/ISRCTN36259164 ) with number 36259164.